Effects of MATAS Hopscotch technique in the learning of subtraction of fraction among year 5 pulils - Periasamy, Devaki (2014)
MATAS Hopscotch technique was created to solve the subtraction of fractions. The study involved 56 pupils from two Year 5 classes. A quasiexperimental, nonrandomized control group, pre-test-post-test delayed posttest was conducted to test the effectiveness of the MATAS Hopscotch technique. The findings indicated the control group showed improvement in pupils’ scores after the implementation of the traditional method with gain scores 9.46. The findings also indicated the experimental group showed improvement in pupils’ scores after the implementation of the MATAS Hopscotch technique with gain scores 15.57. The Analysis of Covariance (ANCOVA) revealed the pupils who were exposed to the use of MATAS Hopscotch achieved significantly better scores as compared with those who were taught using the traditional method. The Two-way ANOVA also showed there were interactions between pupils with different ability. The study also revealed the treatment maintained gains after 8 weeks. The study described types of error made by the pupils in solving the subtraction of fractions. The findings in the pre-test showed both groups made whole number concept errors, directions errors and careless errors. However, in the post-test, the experimental group made only careless errors while the control group made whole number concept errors, directions errors and careless errors. The average and low abilities pupils in the experimental group made only careless errors. The average ability pupils in the control group made directions errors and careless errors while the low ability pupils in the control group made whole number concept errors, directions errors and careless errors. Further, pupils in the experimental group showed a positive attitude towards the MATAS Hopscotch technique. Both the average ability and low ability pupils in the experimental group also showed a positive attitude towards the technique. Hence, we can conclude that MATAS Hopscotch technique was effective in improving pupils’ performances.